Synthesis of Nickel Sulfide Thin Films and Nanocrystals from the Nickel Ethyl Xanthate Complex - Patience Adei Kotei; Nathaniel Owusu Boadi; Selina Ama Saah; Michael Baah Mensah (Advances in Materials Science and Engineering)
Nickel sulfides have unique and diverse structural features, making them ideal for energy conversion and storage. This research focuses on the synthesis and characterization of nickel sulfide thin films and nanocrystals from nickel ethyl xanthate complex using spin-coating and solventless methods. The nickel ethyl xanthate complex (C6H10S4NiO2) was characterized using Fourier-transformed infrared (FT-IR), ultraviolet-visible (UV-Vis), and nuclear magnetic resonance (NMR) spectroscopies as well as thermogravimetric analysis (TGA). The NiS thin films and nanoparticles were analyzed with energy dispersive X-ray (EDX) spectroscopy and X-ray diffraction (XRD). Nickel ethyl xanthate was synthesized in an 81.2% yield. The bandgaps of the nickel sulfide obtained from the spin-coating method ranged from 4.35–4.88 eV. For the solventless method, the bandgap of the nickel sulfide ranged from 3.93–3.96 eV. The crystal phase observed from the spin-coating and solventless methods was α-NiS (hexagonal). A direct correlation was observed between annealing temperature, bandgap, and particle size.